The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1590/1809-43921998283299
|View full text |Cite
|
Sign up to set email alerts
|

The species of Notiobia Perty (Coleoptera: Carabidae: Harpalini) from Brazil

Abstract: -The new species Notiobia glabrata, N. maxima and N. pseudolimbipennis are described. A key to the 11 Notiobia (s.str.) species known from Brazil, data about the junior synonym of N. nebrioides Perty, 1830, and Notiobia umbrata Bates, 1882 is a junior different species groups, each distributed from Brazil over the North-Western part of South America, Central America to Mexico.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
2
8
0
2
Order By: Relevance
“…Harpalini is one of the more speciose tribes of Carabidae (Cieglar 2000)and is represented in this collection by 2 genera, Pelmatellus and Notiobia . In the Neotropics, Pelmatellus is a high altitude genus with a body length of < 11mm while Notiobia ’s body length is generally > 10 mm and inhabits lower altitudes (Goulet 1974; and Arndt (1998). The data from this study supports this observation since Notiobia was only found at the 1500 m and 2000 m sites, while Pelmatellus occurred along the entire gradient.…”
Section: Discussionsupporting
confidence: 76%
“…Harpalini is one of the more speciose tribes of Carabidae (Cieglar 2000)and is represented in this collection by 2 genera, Pelmatellus and Notiobia . In the Neotropics, Pelmatellus is a high altitude genus with a body length of < 11mm while Notiobia ’s body length is generally > 10 mm and inhabits lower altitudes (Goulet 1974; and Arndt (1998). The data from this study supports this observation since Notiobia was only found at the 1500 m and 2000 m sites, while Pelmatellus occurred along the entire gradient.…”
Section: Discussionsupporting
confidence: 76%
“…Eight species are seed feeders and belong to the genus Notiobia. Three of the Notiobia species, formerly unknown to science, N. glabrata, N. maxima, N. pseudolimbipennis, have been described by Arndt (1998).…”
Section: Composition Of the Fig Fruit Feeding Carabid Communitymentioning
confidence: 99%
“…Newly hatched adult beetles (teneral) have to migrate from the leached fruit fall site to find a new food source. The two fig seed specialists are of different size (Arndt 1998) and are sympatric on fruit falls. Notiobia flavicinctus is usually less abundant and only about half of the size of the larger species Notiobia pseudolimbipennis.…”
Section: Notiobia Speciesmentioning
confidence: 99%
“…Individuals were collected in various field trips between 1987 and 2019. Identifications were made following the taxonomic keys proposed by Arndt (1998), Martínez (2005), Hoover (2016), Erwin and Henry (2017), and Shpeley et al (2017), and by identification/confirmation by specialists in the family: Terry Erwin (Smithsonian Museum of Natural History, Washington, USA), Danny Shpeley (Strickland Museum, University of Alberta, Edmonton, Canada) and Pierre Moret (Université Toulouse II, France). In addition, some records were confirmed by comparison with high quality images of type material deposited in the Natural History Museum (NHM, London, United Kingdom) and the Museum of Zoology of the University of Sao Paulo (MZUSP, São Paulo, Brazil).…”
Section: Methodsmentioning
confidence: 99%
“…Distribution. Brazil, Bolivia, French Guiana, Nicaragua, Panama, Peru, Suriname (Arndt 1998) Identification. ABL: 11.0-13.0 mm, SBL: 9.75-12.6 mm (♀); ABL: 10.7-13.8 mm, SBL: 10.3-12.7 mm (♂).…”
Section: Figure 1cmentioning
confidence: 99%